Tok Sheikh Duyong: Religion and Industrial Networking Contribution with Pattani - Abdulloh Salaeh; Amran Abdul Halim; Nidzamuddin Zakaria; Ahmad Kamel Mohamed; Zamrie Ibrahim @ Musa; Norhasnira Ibrahim; Adel M Abdulaziz Algeriani; Idi Hamdi (Human Resource Management Academic Research Society, 2024)
Vol 13, Issue 12